2007
DOI: 10.1029/2006ja012046
|View full text |Cite
|
Sign up to set email alerts
|

Global profiles of compressional ultralow frequency wave power at geosynchronous orbit and their response to the solar wind

Abstract: [1] We investigate the global local-time profiles of compressional wave power in three ultralow frequency (ULF) bands corresponding to Pc3, Pc4, and Pc5 pulsations using magnetic field data from the geosynchronous GOES satellites. The global power profiles of the three frequency bands are studied for low, moderate, and high levels of geomagnetic activity based on the Dst index. We also consider the seasonal variation of the ULF power profiles, as well as the effects of solar wind and interplanetary magnetic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…ULF oscillations are of particular interest for their potential role in energizing the outer electron radiation belt through drift‐resonance interactions and through radial diffusion [ Elkington et al , 1999; Shprits et al , 2008]. During long intervals of fast wind the electron radiation belt is energized in particular [ Paulikas and Blake , 1979; Reeves et al , 2011] and the levels of ULF magnetic field oscillations inside the magnetosphere is seen to be high during those intervals [ Anderson et al , 1990; Sanny et al , 2007; Borovsky and Denton , 2010b]. This is also a time when the velocity shears in the solar wind are plentiful (cf.…”
Section: Discussionmentioning
confidence: 99%
“…ULF oscillations are of particular interest for their potential role in energizing the outer electron radiation belt through drift‐resonance interactions and through radial diffusion [ Elkington et al , 1999; Shprits et al , 2008]. During long intervals of fast wind the electron radiation belt is energized in particular [ Paulikas and Blake , 1979; Reeves et al , 2011] and the levels of ULF magnetic field oscillations inside the magnetosphere is seen to be high during those intervals [ Anderson et al , 1990; Sanny et al , 2007; Borovsky and Denton , 2010b]. This is also a time when the velocity shears in the solar wind are plentiful (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Sanny et al . [] found that the IMF cone angle did not correlate significantly with compressional Pc5 wave power at geosynchronous orbit when compared with pristine solar wind pressure and flow speed correlations. The statistical results from these studies casts doubt on the importance (relative to other energy sources) of the ion foreshock as a driver of Pc5 ULF wave activity.…”
Section: Introductionmentioning
confidence: 95%
“…Then the magnetic field data are filtered with the 150 s to 600 s band‐pass filter (ULF Pc5 wave frequency band), and we use the maximum value of the filtered magnetic field magnitude for the 12 h prior and 12 h after the zero epoch time for each event in the three categories (ICME, SIR, and Alfénic) to represent the amplitude of the ULF wave activity. Sanny et al [] found a local time dependence of ULF wave power, which varies by at most 1 order of magnitude during strong magnetic storms. However, the variation pattern of the ULF wave power shows to be a two‐cycle sinusoidal function, while the peaks of the two cycles (∼12 h interval) change by at most half an order (the wave amplitude change at most a quarter order).…”
Section: Methodsmentioning
confidence: 99%